Process development for cell aggregate arrays encapsulated in a synthetic hydrogel using negative dielectrophoresis. Issue 7 (11th March 2013) - Abdallat, Rula G.; Ahmad Tajuddin, Aziela S.; Gould, David H.; Hughes, Michael P.; Fatoyinbo, Henry O.; Labeed, Fatima H.
Abstract : Spatial patterning of cells is of great importance in tissue engineering and biotechnology, enabling, for example the creation of bottom‐up histoarchitectures of heterogeneous cells, or cell aggregates for in vitro high‐throughput toxicological and therapeutic studies within 3D microenvironments. In this paper, a single‐step process for creating peelable and resilient hydrogels, encapsulating arrays of biological cell aggregates formed by negative DEP has been devised. The dielectrophoretic trapping within low‐energy regions of the DEP‐dot array reduces cell exposure to high field stresses while creating distinguishable, evenly spaced arrays of aggregates. In addition to using an optimal combination of PEG diacrylate pre‐polymer solution concentration and a novel UV exposure mechanism, total processing time was reduced. With a continuous phase medium of PEG diacrylate at 15% v/v concentration, effective dielectrophoretic cell patterned arrays and photo‐polymerisation of the mixture was achieved within a 4 min period. This unique single‐step process was achieved using a 30 s UV exposure time frame within a dedicated, wide exposure area DEP light box system. To demonstrate the developed process, aggregates of yeast, human leukemic (K562) and HeLa cells were immobilised in an array format within the hydrogel. Relative cell viability for both cells within the hydrogels, after maintaining them in appropriate iso‐osmotic media, over a week period was greater than 90%.